Porous Polymers by Controlling Phase Separation during Vapor Deposition Polymerization. Issue 22 (9th October 2013) - Tao, Ran; Anthamatten, Mitchell
<x xml:space="preserve">Abstract</x> A template‐free method is described to fabricate continuous‐phase, porous polymer films by simultaneous phase separation during vapor deposition polymerization. The technique involves concurrent polymerization, crosslinking, and phase separation of condensed species and reaction products. Deposited films form open‐cell, macroporous structures consisting of crosslinked and glassy poly(glycidyl methacrylate). By limiting phase separation during vapor phase deposition, spatially dependent morphologies, such as layered morphologies, can be grown. Results show that combining vapor deposition polymerization with phase separation establishes morphological control, which may be applied to applications including cellular scaffolds, thin cushions and vibration dampers, and membranes for separations. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>